2019
DOI: 10.1002/jcp.28462
|View full text |Cite
|
Sign up to set email alerts
|

VEGF inhibition alters neurotrophin signalling pathways and induces caspase‐3 activation and autophagy in rabbit retina

Abstract: This study sought to evaluate the prospective role exerted by vascular endothelial growth factor (VEGF) in the modulation of nerve growth factor (NGF) and brain‐derived neurotrophic factor (BDNF) signalling pathways in the rabbit retina. To reach this aim, the anti‐VEGF agents aflibercept and ranibizumab were used as a pharmacological approach to evaluate the putative consequences elicited by VEGF inhibition on neurotrophin signalling. VEGF inhibition determined a marked imbalance in proneurotrophin expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…NTs are initially synthetized as pro-neurotrophins (pro-NTs), high molecular weight precursors of 240–260 amino acids. Pro-NTs are proteolytically cleaved by proteases to obtain mature neurotrophins with a molecular weight of approximately 13–14 kDa [ 14 , 15 ]. The production of mature NTs is cell-tissue dependent and their expression pattern may vary according to cell context and physiopathological condition [ 7 ].…”
Section: Neurotrophins: From Cell Signaling To Metabolic Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…NTs are initially synthetized as pro-neurotrophins (pro-NTs), high molecular weight precursors of 240–260 amino acids. Pro-NTs are proteolytically cleaved by proteases to obtain mature neurotrophins with a molecular weight of approximately 13–14 kDa [ 14 , 15 ]. The production of mature NTs is cell-tissue dependent and their expression pattern may vary according to cell context and physiopathological condition [ 7 ].…”
Section: Neurotrophins: From Cell Signaling To Metabolic Processesmentioning
confidence: 99%
“…The mechanism by which BDNF suppresses autophagy seems to be ascribable to the activation of the TrkB signaling pathway. Specifically, it has been well-established that TrkB activation by BDNF elicits PI3K/akt/mTOR pathway, which is one of the most critical negative regulators of autophagy induction [ 15 ]. Similar to what was observed for BDNF, recent findings show that both NT-3 and NT-4 acts as autophagy inhibitors in different physiopathological conditions, such as colorectal cancers and functional recovery after spinal cord injury [ 99 , 100 ].…”
Section: Neurotrophins: From Cell Signaling To Metabolic Processesmentioning
confidence: 99%
“…Reduced VEGF expression can block DHF activity by inhibiting the phosphorylation of TrkB protein. Consistent with this notion, Segatto et al reported that VEGF neutralization by anti-VEGF specific antibodies inhibited the phosphorylation of TrkB protein, inducing apoptosis and autophagy in rabbit retina [ 48 ]. Degradation of HIFs after exposure to hyperoxia results in lower total protein level of TrkB [ 49 ], reducing the ability of DHF to exert a protective effect.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, a wide variety of other proteins (BDNF and CREB) [52,[54][55][56] and signaling pathways (MAPKs and AKT) [127] are also involved in these processes. The BDNF, as a member of the neurotrophins group, prompts the MAPK/ERK signaling pathways, neural survival, growth, and differentiation and improves synaptic plasticity and repair mechanisms [128,129]. In addition to the BDNF, the CREB, as a translation factor, has a signi cant effect in neuronal survival [130].…”
Section: Discussionmentioning
confidence: 99%